2008
DOI: 10.1007/s11481-008-9142-2
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Microglial Activation During Neuroinflammation and Alzheimer’s Disease

Abstract: Microglial activation is an important pathogenic component of neurodegenerative disease processes. This state of increased inflammation is associated not only with neurotoxic consequences but also neuroprotective effects, e.g., phagocytosis and clearance of amyloid in Alzheimer's disease. In addition, activation of microglia appears to be one of the major mechanisms of amyloid clearance following active or passive immunotherapy. Imaging techniques may provide a minimally invasive tool to elucidate the complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
105
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 172 publications
(232 reference statements)
3
105
0
6
Order By: Relevance
“…Despite the classical hypothesis of the cytotoxic features of activated microglia, recent evidences suggest that microglia are protective in the early stages of AD by promoting amyloid phagocytosis and clearance of fibrillar and soluble amyloid. Microglia can be activated towards a classical proinflammatory phenotype, but also to a neuroprotective phenotype (Venneti et al, 2009). Early microglial activation has been attributed to a neuroprotective role in amyloid pathology, promoting Ab clearance (Yan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the classical hypothesis of the cytotoxic features of activated microglia, recent evidences suggest that microglia are protective in the early stages of AD by promoting amyloid phagocytosis and clearance of fibrillar and soluble amyloid. Microglia can be activated towards a classical proinflammatory phenotype, but also to a neuroprotective phenotype (Venneti et al, 2009). Early microglial activation has been attributed to a neuroprotective role in amyloid pathology, promoting Ab clearance (Yan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Activated microglia thus represent an important marker of neuroinflammation (for a recent review see Venneti et al, 2009). This has been confirmed in a large number of studies that have shown that levels of TSPO and/or microglia are greatly increased in examples of inflammation (as reviewed by Chen and Guilarte, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the expression of TSPO is a marker of choice to study the extent and role of neuroinflammation in several neurological disorders with the use of radiolabeled TSPO-targeted compounds (Cagnin et al, 2007;Venneti et al, 2009b;Winkeler et al, 2010).…”
Section: Supplementary Introductionmentioning
confidence: 99%